Profil Fitokimia dari Minyak Atsiri Cascara Kopi Robusta Lampung (Coffea canephora) - Destra Mika Novtasari Damanik (BEST Journal (Biology Education, Sains and Technology), 2025)
This research evaluates the influence of fruit maturity level (red bean and green bean) and extraction methods on the phytochemical profile of essential oil derived from cascara of robusta coffee (Coffea canephora) from Lampung. Extraction was carried out using steam distillation, hydrodistillation, and Soxhlet methods, with compound analysis performed via GC-MS. The results showed that the Soxhlet method was the most effective, yielding the highest amount of essential oil from green bean cascara (5.5%) compared to red bean (4.75%). The phytochemical profile of green bean cascara was dominated by caffeine (75.59%), phenols (8.3%), and quinic acid (6.99%), while red bean cascara contained caffeine (62.12%), phenolic compounds (11%), and Maillard reaction products. Only five compounds were shared between both samples. In conclusion, the maturity level of coffee fruit and the extraction method significantly affect the phytochemical content and yield of essential oil from robusta coffee cascara.